Performance of Dipterocarpus macrocarpus (Hollong) Seedlings under Different Intensities of Light - Beniwal, B. S. (Indian Forester, 1990)
An experiment was taken up during 1984 at Lathaw (Arunachal Pradesh) to work out requirement of optimum light intensities for height growth of Hollong seedlings. In all 25 treatments with three replications were taken. Among the all treatments T17 (25% overbead and 100% side shade) proved to be the best. It was also observed that side shade played vital role than overbead shade.